Improving Reading Ability Using Big Book Media in Class I Students at SDN 2 Bulango Utara - Adju, Olyan S.; Adiko, Hendra Saputra S.; Ishak, Irmawati Duko (Journal of Education Review Provision, 2023)
This research aimed to improve reading skills using Big Book media for grade 1 students at SDN 2 Bulango Utara. The type of research used is classroom action research, with the research subject being a grade I student totaling 27 students. This research was carried out in the form of cycles, and each cycle consisted of 4 stages, namely the planning stage, the implementation stage, the observation, and the reflection stages. This research shows that students’ reading ability in Indonesian language subjects is still in the low category. This is indicated by the low reading ability of students at the time of the initial observation reaching 37.03% with capable criteria, and the reading ability of students in cycle I of 62.96% in capable criteria with a fairly good category, while the reading ability of students in cycle II increased by 100% with very good categories in capable criteria. The application of Big Book learning media can improve students’ reading skills in class I at SDN 2 Bulango Utara, Bone Bolango Regency. The achievement of providing action from cycle I to cycle II researchers ended the meeting in cycle II third meeting because it had met the predetermined performance indicators of 80%.